2014
DOI: 10.1212/wnl.0000000000000638
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective randomized trial of venous angioplasty in MS (PREMiSe)

Abstract: This is a Class I study demonstrating that clinical and imaging outcomes are no better or worse in patients with MS identified with venous outflow restriction who receive venous angioplasty compared to sham controls who do not receive angioplasty. This study also includes a Class IV phase 1 study of safety in 10 patients receiving the angioplasty procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 35 publications
0
47
0
1
Order By: Relevance
“…Finally, a recently published class I sham‐controlled, randomized, double‐blind study investigating the safety and efficacy of venous angioplasty in MS patients fulfilling ultrasound criteria of CCSVI showed that venous angioplasty did not improve hemodynamic parameters in terms of venous hemodynamic insufficiency severity score as well as clinical outcomes in terms of annualized relapse rate, Expanded Disability Severity Score, and MS Functional Composite (Siddiqui et al. ). Moreover, “Liberation treatment” exacerbated underlying disease activity in terms of new T2 and gadolinium‐enhancing T1 lesions (Siddiqui et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a recently published class I sham‐controlled, randomized, double‐blind study investigating the safety and efficacy of venous angioplasty in MS patients fulfilling ultrasound criteria of CCSVI showed that venous angioplasty did not improve hemodynamic parameters in terms of venous hemodynamic insufficiency severity score as well as clinical outcomes in terms of annualized relapse rate, Expanded Disability Severity Score, and MS Functional Composite (Siddiqui et al. ). Moreover, “Liberation treatment” exacerbated underlying disease activity in terms of new T2 and gadolinium‐enhancing T1 lesions (Siddiqui et al.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, “Liberation treatment” exacerbated underlying disease activity in terms of new T2 and gadolinium‐enhancing T1 lesions (Siddiqui et al. ). In line with these findings, two recent open‐label, retrospective studies also showed an increase in disease activity irrespective of adherence to disease‐modifying therapies in patients with MS with CCSVI who underwent venous angioplasty (Alroughani et al.…”
Section: Resultsmentioning
confidence: 99%
“…Findings from some of these studies showed positive effect of the treatment while other studies not only showed no potential treatment benefit even increase in disease activity reported. In an RCT by Siddiqui et al [5] patients with MS and extra cranial venous abnormality proved by Doppler Sonography criteria underwent venoplasty. it is showed that clinical and imaging outcomes are no better or worse in patients with MS identified with venous outflow restriction who receive venous angioplasty compared to sham controls who do not receive angioplasty [5].…”
Section: Discussionmentioning
confidence: 99%
“…CCSVI was described as a state of chronic impaired venous drainage from the central nervous system (CNS) and Zamboni et al regarded it as a potential cause of MS when there is 2 out of 5 Echo colored Doppler (ECD) Zamboni criteria [5]. This was followed a small open-label studies conducted to evaluate the effect of endovascular angioplasty in MS patients with CCSVI, a procedure known as "Liberation surgery [11,12]. It has been hypothesized that CCSVI might lead to clinically overt Multiple sclerosis either due to activation an autoimmune reaction by cerebrovascular endothelium in the setting of refluxing blood flow [13], or due noxious activity of iron deposit which can be stored in brain parenchyma as a result of break down in blood brain barrier [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although subsequent clinical research has failed to support this hypothesis [16][17][18], the debate currently continues over whether the relationship is real. Echo colored Doppler was widely used to assess CCSVI in MS [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Magnetic resonance venography (MRV) have been used with less sensitivity in detecting intraluminal jugular defects [19,20] while venography was used by Yamout et al [21].…”
Section: Introductionmentioning
confidence: 99%